Studi Eutrofikasi Akibat Aktivitas Penggunaan Lahan di Danau Buyan - Ida Bagus Ketut Gede Kertia; I Wayan Arthana; I Wayan Sandi Adnyana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2018)
ABSTRACT EUTROPHIC STUDY TO EVALUATE THE IMPACT OF LAND USE ACTIVITY IN BUYAN LAKE Increased in land use activity in Buyan Lake catchment area can be a threat to multifunction of the lake. Identification the impact due to land use activity is to important of lake management. This study aims to know the land use and its activities, predicted the yield of sediment and nutrient losses, and knew of trophic state for the lake. The Lake Buyan catchment area is 1,943.8 ha. This research use survey method and in situ and ex situ measurement from March to May 2017. Type of data collected were land use and its activities, C-organic and soil nutrient, and variables of trophic state for the lake. This study showed that dryland vegetables crops with bench terrace by low standard contruction, shrub with grass, and coffee plantation with traditional terrace with area each of 71.9 ha (3.7%), 43.0 ha (2.2%), and 25.4 ha (1.3%) respectively has an erosion of higher than tolerable soil loss. The sediment yield and C-organic, nitrogen, phosphate and potassium losses with the amount each of 9,399.4, 266.6, 14.5, 15.8, and 58.7 ton year-1 respectively, and with soil and water conservation practices is very effective to reduced the sediment yield and C-organic, nitrogen, phosphate and potassium losses with the amount each of 3,160.1, 89.6, 4.9, 5.3, and 19.7 ton year-1. Average of nitrogen, phosphate, chlorophyll a, and tranparency with the value each of 3,500, 118.4, 48.2 µg L-1 and 1.8 m showed that trophic state for Buyan Lake is euthrophic until hypereuthrophic, and a moderate euthrophic indicated from the average TSI with the value of 64.3. Key words : Buyan Lake, land use, erosion, sediment yield, eutrophic